Anthopleura dalyae sp. nov. (Cnidaria: Actiniaria), a new species of sea anemone from the southern Gulf of Mexico - González Muñoz, Ricardo Enrique (2019)
Anthopleura dalyae sp. nov, a new species of sea anemone (Actiniaria: Actiniidae) from the rocky intertidal zone of La Gallega reef, Veracruz, Mexico, is described and illustrated. This species is characterized by a column that is pale yellow proximally and dark-orange to bright-orange distally, longitudinal rows of verrucae from margin to limbus, and a series of marginal projections with acrorhagi. Anthopleura dalyae sp. nov. is distinguished from other species of Anthopleura from the Gulf of Mexico by several taxonomic characters, such as column coloration, number of tentacles, variable number of directive mesenteries and siphonoglyphs, as well as some differences on cnidae. Anthopleura dalyae sp. nov. is the fourth species of the genus occurring in shallow intertidal waters associated to coastal and coral reef environments of the region, and the third species of the genus Anthopleura recorded in the southern Gulf of Mexico.